The Knowledge of Hepatitis B Infection And Practice Towards Its Prevention Among Pregnant Women - Kanikwu, Phoebe Nwamaka; Onukwu, Patricia Udo; Olaniyan, Mathew Folaranmi; Muhibi, Musa Abidemi (Nursing and Health Sciences Journal (NHSJ), 2024)
Infection with Hepatitis B remains a health challenge across the globe. This descriptive survey focused on the knowledge of hepatitis B infection (HBI) and prevention practices of pregnant women. Thus, this study assessed knowledge of HBI, HBI prevention practices, factors affecting the practice of HBI prevention among pregnant women, the association between the socio-demographic characteristics cum knowledge of HBI, as well as the relationship between the knowledge of HBI and the prevention practices. Balloting with replacement was employed in selecting 267 pregnant women attending an antenatal clinic in Delta State, Nigeria. The instrument for data collection was a Questionnaire developed by the researchers. The reliability of the instrument was conducted using Cronbach alpha which yielded coefficient of 0.738. Data collected were analyzed using frequencies, percentages, mean, Kruskal Walis test and Chi-Square statistic test. Majority of the study respondents (53.8%) had low level of knowledge about HBI but 60% had good level of prevention practice. 36.7% of the pregnant women believed that they had a low-risk status for HBI, 43.4% that prayer was more effective than vaccine and 60.7% that herbal medicine was available to prevent HBI. Significant association did not exist between pregnant women’s socio-demographic characteristics and their knowledge of HBI (k=2.92, p-value=0.10). Significant relationship existed between knowledge of HBI and the prevention practices of pregnant women (X2=36.71; p-value=0.001). Findings showed that the pregnant women had a low knowledge level for hepatitis B virus but a good level of prevention practice possibly due to high level of provider-initiated preventive services. Nurses should organize more detailed health education sessions on hepatitis B infection to pregnant women and keep up with their role of performing provider-initiated preventive services.